Dr. Jonathan Stokes: Machine Learning & Novel Antibiotics - Zhang, Eric; Chu, Natalie; Zhang, Yiming (The Meducator, 2022)
Dr. Jonathan Stokes is an Assistant Professor in the Department of Biochemistry and Biomedical Sciences at McMaster University. He received his BHSc in 2011 and his PhD in antimicrobial chemical biology in 2016, both from McMaster University. He then completed a postdoctoral fellowship at the Broad Institute of MIT and Harvard. In 2021, Dr. Stokes established his lab back at McMaster University, which, in part, leverages machine learning approaches to discover new antibiotics. The Stokes Lab also seeks to determine the molecular mechanisms underlying antibiotic tolerance and resistance. Furthermore, he is the co-founder of the non-profit Phare Bio, dedicated to navigating earlystage antibiotics through preclinical trial